Development and expert validation of a competition management model for basic artistic swimming strokes - Danardani, Wasti; Hidayat , Syarif (Journal Sport Area, 2025)
Background: Artistic swimming in Indonesia has grown slowly due to limited participation and the absence of standardized regulations at the beginner level. Although basic stroke events are often held, they lack a consistent and validated competition system, creating a gap that reduces fairness and hampers athlete development. Objectives: This study aimed to design and validate a standardized management model for basic stroke artistic swimming competitions. Methods: Research and development (R&D) following Borg and Gall was applied at the expert validation stage. Ten nationally and internationally certified judges evaluated the model using a 5-point Likert scale covering arena layout, personnel duties, and scoring procedures. Data were analyzed descriptively, with ≥ 3.5 considered valid. Finding/Results: Expert evaluation indicated a high level of feasibility (mean score = 4.6), confirming that the proposed model aligns with international guidelines and is suitable for implementation. Experts agreed that the competition arena, personnel structure, and integrated scoring system—which combines technique execution and swimming speed—provide fair and objective evaluation for beginner-level athletes. Conclusion: The validated model offers the first standardized management framework for basic stroke artistic swimming competitions in Indonesia, supporting consistent event organization and nurturing athlete development. However, the current study is limited to expert assessment. Further field trials involving real competition settings are required to determine the model’s effectiveness in practice.